Green Synthesis Zinc Nanoparticles in the Treatment of Heavy Metals in the form of Complexes - Muslim Abdullah, Suzan; AL-Hamdani, Abbas Ali Salih; Resheed, Farqad Abdullah (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
Myrtle plant was washed, dried, and powdered after harvesting to produce a fine powder that was used in water treatment. created an alcoholic extract from the myrtle plant using ethanol, which was then analyzed using GC-Mass, Fourier Transform Infrared spectroscopy, and ultraviolet-visible spectroscopy to identify the active components. Zinc nanoparticles were created using alcoholic extract. We used FTIR, UV-Vis, SEM, EDX, and TEM to characterize zinc nanoparticles. Using a continuous processing procedure, zinc nanoparticles with myrtle extract and powder were employed to clean polluted water containing heavy metals. Firstly used 2g with 20ml polluted water and the result was ( Fe 96.20%, Cr 84%, Pb 100%, Sb 93.70, Cd 100%, andCu 90.60%) Secondly, weused Zinc nanoparticles to treat water the result was (Fe 96.20%, Cr 84%, Sb 54%, 64.50%, Cu 64.80). When Comparing between results myrtle powder and zinc nanoparticle we found myrtle plant was prefer in treatment water.